2004
DOI: 10.1128/aac.48.1.168-171.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Synergy Studies of Stenotrophomonas maltophilia Isolates from Patients with Cystic Fibrosis

Abstract: Stenotrophomonas maltophilia is a newly emerging pathogen being detected with increasing frequency in patients with cystic fibrosis (CF). The impact of this multidrug-resistant organism on lung function is uncertain. The optimal treatment for S. maltophilia in CF patients is unknown. We studied the in vitro activity of ten antimicrobial agents, and conducted synergy studies by using checkerboard dilutions of eight pairs of antimicrobial agents against strains isolated from 673 CF patients from 1996 to 2001. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 32 publications
2
51
1
Order By: Relevance
“…Gram-positive pathogens were responsible for 71.71% of the total isolates. The ratio of Gram-positive pathogens to Gram-negative pathogens was about 3.52 : 1, which appeared much higher than that observed in studies from other countries [19,20,26]. Reasons for this difference may include population differences in colonization, genetic differences in immune response and possibly geographic differences in laboratory techniques for pathogen isolation and reporting [27].…”
Section: Discussioncontrasting
confidence: 44%
“…Gram-positive pathogens were responsible for 71.71% of the total isolates. The ratio of Gram-positive pathogens to Gram-negative pathogens was about 3.52 : 1, which appeared much higher than that observed in studies from other countries [19,20,26]. Reasons for this difference may include population differences in colonization, genetic differences in immune response and possibly geographic differences in laboratory techniques for pathogen isolation and reporting [27].…”
Section: Discussioncontrasting
confidence: 44%
“…The high rate of resistance found in this study serves to underline the resistant nature of S. maltophilia present in the Scottish CF population. Co-trimoxazole, ticarcillin/clavulanate, minocycline, doxycycline, levofloxacin, and chloramphenicol have all been reported as being the most active single agent against S. maltophilia isolated from individuals with and without CF (6,9,11,18,22,27,29). Co-trimoxazole is often the drug of first choice for therapy, although increasing in vitro resistance is being reported (2,9,14).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, the frequency of viral infections was similar in cf patients when compared to healthy controls, but these infections were more frequently associated with lower respiratory tract symptoms 43 . Furthermore, epidemiological studies showed a seasonal pattern of first P. aeruginosa acquisition 44 and development of chronic P. aeruginosa infection and a rise in P. aeruginosa antibodies with rsv infections suggesting the influence of respiratory viruses 45 . The possible interaction between respiratory viruses and bacteria was suggested from in vitro studies, showing increased adherence of P. aeruginosa to airway epithelial cells during viral infection and direct binding between P. aeruginosa and rsv 46;47 .…”
Section: Co-infectionsmentioning
confidence: 99%
“…Most data on the treatment of S. maltophilia come from case reports or in vitro studies 43 . San Gabriel et al investigated isolates from 673 cf patients and studied the in vitro activity of ten antimicrobial agents against these isolates, also performing synergy studies 44 . Doxycycline was most active, inhibiting 80% of isolates.…”
Section: Managementmentioning
confidence: 99%